Thoracal Segmental Spinal Anesthesia for Lower Back Lipoma Excision - Christanto Suryo; I Wayan Widana (PT Dexa Medica, 2022)
Background: General anesthesia is the most preferred anesthetic management for lower back surgery, considering the location and practicality. However, multiple studies showed that regional anesthesia, particularly thoracal segmental, spinal anesthesia, had more advantages compared to general anesthesia. Case presentation: We report a 19-year-old woman admitted to the OR for infected lipoma in lower back region, located in thoracal 12th, who underwent successful thoracal segmental spinal anesthesia. Conclusion: This is an original case report which showed significance of thoracal segmental spinal anesthesia and the advantages compared to general anesthesia.